2020
DOI: 10.1016/j.molcel.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

PRC1 Catalytic Activity Is Central to Polycomb System Function

Abstract: Highlights d PRC1 catalysis drives PRC2 occupancy and H3K27me3 deposition at target sites d cPRC1 binding and PRC1-mediated chromatin interactions require PRC1 catalysis d DNA-binding vPRC1 complexes occupy target sites independently of PRC1 catalysis d PRC1 catalytic activity is essential for Polycomb-mediated gene repression

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
211
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(230 citation statements)
references
References 125 publications
(196 reference statements)
18
211
1
Order By: Relevance
“…However, our measurements revealed that Polycomb bodies 192 accounted for just 1.3% of the total nuclear volume and that RING1B fluorescence signal 193 inside Polycomb bodies was only 1.3-fold more intense than the surrounding nucleus ( Figure 194 2J). This means that only 1.7% of total PRC1 signal originates from Polycomb bodies, 195 consistent with evidence from ChIP-seq experiments that PRC1 also binds more stably to 196 thousands of other smaller target sites in the genome (Blackledge et al, 2020;Endoh et al, 197 2012; Kloet et al, 2016;Morey et al, 2013). Therefore, PRC1 binds chromatin more stably at 198…”
Section: Only a Fraction Of Chromatin Bound Prc1 Displays Stable Bindsupporting
confidence: 52%
“…However, our measurements revealed that Polycomb bodies 192 accounted for just 1.3% of the total nuclear volume and that RING1B fluorescence signal 193 inside Polycomb bodies was only 1.3-fold more intense than the surrounding nucleus ( Figure 194 2J). This means that only 1.7% of total PRC1 signal originates from Polycomb bodies, 195 consistent with evidence from ChIP-seq experiments that PRC1 also binds more stably to 196 thousands of other smaller target sites in the genome (Blackledge et al, 2020;Endoh et al, 197 2012; Kloet et al, 2016;Morey et al, 2013). Therefore, PRC1 binds chromatin more stably at 198…”
Section: Only a Fraction Of Chromatin Bound Prc1 Displays Stable Bindsupporting
confidence: 52%
“…PRC1 modulates both the structure and modification state of chromatin; functions grossly ascribed to canonical and non-canocial PRC1 respectively (Grau et al 2011;Isono et al 2013;Blackledge et al 2014;Rose et al 2016;Kundu et al 2017;Blackledge et al 2019;Plys et al 2019;Tatavosian et al 2019). What then is the relative contribution of these functions to gene represion?…”
Section: Prc1 Functionality and Gene Expressionmentioning
confidence: 99%
“…Recent studies have suggested a highly regulated hierarchical recruitment model involving a complex crosstalk between the activities of the different PRC1 and PRC2 complexes in the establishment of polycomb heterochromatin domains (3,10). The loss of H2AK119ub1 on polycomb target genes has been observed to result in a corresponding reduction in H3K27me3 deposition, suggesting a strong connection between PRC1 and PRC2 catalytic activities (11,12). However, the specific role played by PRC1-mediated H2AK119ub1 in the recruitment of PRC2 has remained elusive, and there have been conflicting observations reporting both inhibition and activation of PRC2 by this histone mark (13,14).…”
mentioning
confidence: 99%